Landscape degradation in the world and in Hungary - Kertész, Ádám; KřečekJosef (Hungarian Geographical Bulletin, 2019)
The concept of landscape degradation interprets the process in landscape ecological sense, i.e. the degradation of one landscape forming factor leads to the degradation of the whole landscape. The consequence is a persistent decline in land productivity and in the provision of other ecosystem services. Global environmental change is driven mainly by human influence in the Anthropocene with an exponentially growing significance in time. Global environmental processes are very much interrelated. Because of population growth more food, fibre, clean water, energy etc. will be needed and there are two ways to achieve this, either to gain new areas for cultivation by changing present land use or to intensify cultivation in the areas with the best conditions for cultivation. Deforestation and forest degradation are dealt with in detail in the paper. The introduction of soil degradation processes follows the system given in the EEA Environmental Assessment Report (2003). The effect of landscape degradation on ecosystem services is well explained by the fact that approximately 20 per cent of the Earth’s vegetated surface shows persistent declining trends in productivity, mainly as a result of land/water use and management practices (UNCCD 2017). Landscape degradation processes of Hungary are discussed in the paper, including sheet, gully and wind erosion, soil sealing, salinization, physical degradation, landslides, desertification. An estimation of the aesthetical value of the landscape is provided as well concluding that the surface of the country represents a relatively high aesthetical value. The main conclusion is that Hungarian landscapes are well maintained and they belong to the most precious European landscapes. It should be added that all degradation processes represent important environmental problems to be combatted on the basis of a well-established policy making.